Angel time [large type] : a novel - Rice, Anne, 1941- (Rice, Anne, 1941- Songs of the seraphim, 2009)
Toby O'Dare, a contract killer of underground fame is on assignment to kill once again. Into O'Dare's nightmarish world of lone and lethal missions comes a mysterious stranger, a seraph, who offers him a chance to save rather than destroy lives. O'Dare, who long ago dreamt of being a priest but instead came to embody danger and violence, seizes his chance.